IMPLEMENTASI KONSEP PARIWISATA BERBASIS MASYARAKAT DALAM PENGELOLAAN PANTAI KEDONGANAN - Suasapha, Anom Hery (JURNAL MASTER PARIWISATA; Volume 02, Nomor 02, Januari 2016, 2016)
Kedonganan beach is a tourist destination located in Kedonganan Village, South Kuta, Bali, known for its scenic beauty and the culinary activity. The beach was a fisherman village, until tourism developed in the area during 1995. The tourism development was not a carefully planned, resulted in many negative effects on the area and also to the community. A correction plan was developed based on Community Based Tourism (CBT) concept, and has been implemented since 2006. This article discusses the implementation process of community based tourism (CBT) in Kedonganan Beach. The enabling factors and the barrier of the implementation are also discussed, and the model of CBT implemented in the area are developed and discussed. The analysis result shows that implementation of CBT concept in the management of Kedonganan has been done in two steps. These steps were devided into smaller steps, in which four CBT principles were implemented. Local inisiative, support from Badung Regency Government and social capital were some of the factors that enables the implementation of CBT concept in Kedonganan Beach, while rejection from some of the community member and different perception of the community toward the lagal status of the land were the barriers of the implementation.
Keywords: Kedonganan Beach; community based tourism; implementation; enabling and barrier factors; CBT Model